2017
DOI: 10.1097/md.0000000000006873
|View full text |Cite
|
Sign up to set email alerts
|

The structural changes of upper airway and newly developed sleep breathing disorders after surgical treatment in class III malocclusion subjects

Abstract: Bimaxillary surgery is the traditional treatment of choice for correcting class III malocclusion which is reported to cause an alteration of oropharyngeal structures and upper airway narrowing that might be a predisposing factor for obstructive sleep apnea (OSA). This study aimed to analyze sleep parameters in class III malocclusion subjects and ascertain the prevalence of snoring or OSA following bimaxillary surgery.A total of 22 patients with Le Fort I osteotomy and mandibular setback for class III malocclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In contrast, the study by Lee et al [ 14 ] showed a decrease in airway space and increase in AHI after bimaxillary orthognathic surgery, with the average maxillary setback and mandibular setback of 1.01 ± 1.54 mm and 8.23 ± 3.59 mm, respectively. The difference between these studies is thought to come from the difference in maxillary movement (5 ± 2.2 mm and − 1.01 mm) despite a similar mandibular setback amount.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, the study by Lee et al [ 14 ] showed a decrease in airway space and increase in AHI after bimaxillary orthognathic surgery, with the average maxillary setback and mandibular setback of 1.01 ± 1.54 mm and 8.23 ± 3.59 mm, respectively. The difference between these studies is thought to come from the difference in maxillary movement (5 ± 2.2 mm and − 1.01 mm) despite a similar mandibular setback amount.…”
Section: Discussionmentioning
confidence: 81%
“…Some of the earlier studies did not report any significant changes being present in the airway space after MS [9, 23, 24]. Several other studies performed using CT, however, suggested that PAS was significantly decreased after MS [2, 3, 1013, 2527]. For example, Lee et al achieved a decrease of 14.07% in the total volume following a mean MS of 9.20 mm [11], while Kim et al reported a decrease of 15.80% in total PAS and decreases of 22.08%, 8.10%, and 12.43% in the oropharynx, nasopharynx, and hypopharynx, respectively, after a mean MS of 8.25 mm [28].…”
Section: Discussionmentioning
confidence: 98%
“…A three-dimensional (3D) PAS volume showed a significant decrease in the oropharyngeal airway, and no significant change has been observed in the sleep symptoms [8]. Reports indicated that bimaxillary orthognathic surgery to reduce PAS played a role, but it does not increase AHI, one of the important determinants of sleep apnea [18,19,21,23]. As a result of a significant decrease in the airway space, it did not influence the AHI-values or cause OSA.…”
Section: Discussionmentioning
confidence: 98%